Knowledge, Attitudes and Practices Regarding Smoking Prevention Among Students of Jakarta Global University - Sabila, Ahda; Budiastuti, Rizky Farmasita; Adina, Anugerah Budipratama; Zhafira, Bilqis; Indriani, Melis (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Students need good knowledge, attitudes, and behavior in maintaining a healthy lifestyle, especially in avoiding smoking and understanding its dangers, to set a good example for the public and younger generations. This study aims to examine the knowledge, attitudes, and practices (KAP) of students regarding smoking habits at Jakarta Global University (JGU). The research uses a descriptive quantitative method with an online questionnaire involving 105 respondents. The results show that most students are aged 18 to 22 years (86.7%), with the majority from the pharmacy department (43.8%). Students' knowledge about the dangers of smoking is quite good, although challenges remain in improving their understanding of the serious health risks. Their attitudes demonstrate strong belief in the effectiveness of anti-smoking campaigns, with 67.6% of respondents agreeing that smoking has a severe negative impact on health. The practice of smoking prevention is also relatively high, with 64.8% of students supporting smoking cessation programs and replacing smoking habits with healthy activities. The study concludes that students' knowledge, attitudes, and behavior regarding smoking habits are generally good. However, further education is needed to ensure effective smoking prevention and reduce the associated health risks.